Israel's approval of West Bank land registration sparks outrage (Le Monde, 2026)
The Israeli government has approved a process to register land in the region as 'state property,' drawing condemnation from Arab nations and critics who said it would accelerate annexation of the Palestinian territory. The European Union called on Israel to reverse the move.
Palestine (Permanent Observer to the UN)